Organic Fertilizer Production From Cattle Waste Vermicomposting Assisted By Lumbricus Rubellus - Siswo Sumardiono; R.P. Djoko Murwono (Chemical Engineering Diponegoro University, 2011)
Composting is decomposition of compound in organic waste by specific treatment using microorganism aerobically. Natural composting for producing organic fertilizer from manure and market waste utilize long time processing and less equal to the market demand. Vermicomposting is a technique to produce high quality compos fertilizer from biodegradable garbage and mixture of red worm (Lumbricus Rubellus). In conventional compos production took 8 weeks of processing time, in vermicomposting only took half processing time of conventional technique. It is occurred by red worm additional ease cellulose degradation contain in manure which is could not decomposed with composting bacteria. The purposes of this research are to investigate the effect of manure comparison to red worm growth and to evaluate the effect of comparison between manure and market waste to red worm growth. This research was conducted by vary the weight of red worm (100 gr, 200 gr, 300 gr, 400 gr, 500 gr) and market waste addition (50 gr, 100 gr, 150 gr, 200 gr, 300 gr). Moreover, 3 kg of manure was mixed by various weight of red worm, while variation of market waste addition was involved 500 gr red worm and 3 kg manure mixture. Optimum increasing weight of red worm that was obtained by 100 gr red worm addition is 160 gr within 2 weeks. In added market waste variation, the highest increasing of red worm was resulted by 50 gr market waste addition, with 60 gr increasing weight of red worm. Production of casting fertilizer was highly effected by composition of used materials such as medium, manure and red worm comparison as well as market waste additional